LITERATION CULTURE OF STUDENT LITERATURE IN INDUSTRIAL REVOLUTION 4.0 - Ekol Pambudianto (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
literacy culture plays an important role in the development of a learning society that lives in the global era or is called the current century of creative-innovative knowledge. The history of human civilization proves that a great nation whose people have a high literacy culture. Literacy culture is hampered by the not yet forming mentality of students' reading and writing culture. Literacy culture must be instilled early in students to ingrained for the sake of achieving a superior generation, quality, and have a strong mind and character to face global challenges. Global developments in various scientific disciplines that are felt now certainly must be recognized by all parties, especially in the school environment. The school environment must make literacy culture the first and foremost door to build the progress of human civilization, society, and the Indonesian people. The mastery of literacy culture for these civilizations is important and should receive serious attention to make their lives more developed/modern, meaningful, and advanced both personally, socially, spiritually, and culturally. One of the ways to achieve and make students mentality is literacy culture is through literature. Literature becomes a creative work that has a distinctive or unique style in the use of its language. Literary creative works record a variety of phenomena in the social life of both real and fictitious ones that instill educational values. Through these various advantages, literary works must be used as an effective stimulus to foster a culture of student literacy. Therefore, literature must be used as the basis for the first and foremost doorstep for the achievement of a superior generation of cultural literacy mentality.